2012
DOI: 10.1590/s0102-86502012000200005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and nutritional status in the late postoperative of pancreaticoduodenectomy: influence of pylorus preservation procedure

Abstract: PURPOSE:To evaluate the nutritional status of patients in the late postoperative period of pancreaticoduodenectomy (PD) and compare the long-term outcome according to pylorus-preserving (PPPD) or the standard technique (SPD) in which the pylorus is resected. METHODS: This prospective study was conducted twelve months prior or more in patients who had underwent PD (PD Group, n=15) and health volunteers (Control Group, n=15). At a post hoc analysis, the PD Group was divided in PPPD Subgroup (n=9) and SPD Subgrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
1
4
0
1
Order By: Relevance
“…Similar trends were observed in mid-arm circumference, triceps skin fold thickness and hand-grip [13]. Others reported that 90% of the patients who had PD surgery recovered their preoperative body weight by 12 months, whereas 60%–85% of the patients recovered their weight by 6 months [101415]. Previous studies stated that malnutrition and weight loss in PD group significantly affect QoL [16].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar trends were observed in mid-arm circumference, triceps skin fold thickness and hand-grip [13]. Others reported that 90% of the patients who had PD surgery recovered their preoperative body weight by 12 months, whereas 60%–85% of the patients recovered their weight by 6 months [101415]. Previous studies stated that malnutrition and weight loss in PD group significantly affect QoL [16].…”
Section: Discussionsupporting
confidence: 65%
“…Park et al [9] reported that relative body weight (RBW) and triceps skinfold thickness (TSFT) had significantly decreased after the surgery and recovered to more than 90% of the preoperative value by 12 months whereas transferrin, albumin (Alb) and protein had returned to preoperative levels by 3 months. Muniz et al [10] reported higher levels of glycemia, alkaline phosphatase, and C-reactive protein (CRP) among the PD group in comparison with control group.…”
Section: Introductionmentioning
confidence: 99%
“…28 Pancreatic exocrine insufficiency was less frequent when pancreas anastomosis was performed in the jejunum (pancreatojejunostomy) rather than in the stomach (pancreatogastrostomy). 28 Pancreatic exocrine insufficiency was less frequent when pancreas anastomosis was performed in the jejunum (pancreatojejunostomy) rather than in the stomach (pancreatogastrostomy).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported 7%–15% weight loss in total gastrectomy patients and 7%–10% weight loss in esophagectomy and pancreatectomy patients postoperatively 95 . The GI dysfunction caused by the surgery eventually resolves, and studies have found that 6–12 months after the operation, most PD patients are able to regain weight to their preoperative baseline 28 , 96 . However, it is unclear if getting them back to baseline faster would provide an additional benefit.…”
Section: The Pancreasmentioning
confidence: 99%
“…Several studies have looked at QOL measures in postoperative pancreatic surgery. Most report significant weight loss postoperatively (mostly specific to PD), with one study reporting 90% of patients able to regain weight in 1 year, 96 whereas another reported 60%–85% of patients regained weight by 6 months 35 . Another study, including total gastrectomies, reported that patients with malnutrition and percent weight change postoperatively had a decreased QOL and more symptoms 95 .…”
Section: The Pancreasmentioning
confidence: 99%